Inflation Modeling In Algeria: Analytical And Econometric Study - Daoudi, Mohammed (Université de M'sila, 2020)
This study aims to model the inflation rate in Algeria, by applying the ARDL model and the Toda-Yamamoto causality test for the period 1990-2018. Through the results, the cause of inflation in Algeria is mainly structural, due to the weakness of domestic production, which increases imports. Although imports into Algeria play the role of an automatic regulator of domestic markets and limit inflation (3.35%), it is also an important channel for imported inflation, and a monetary reason linked to the size of the money supply and the inability to control it (1.1%), while the impact of public spending (0.0252%) and the Algerian dinar exchange rate (0.2949%) remains somewhat limit.
Keywords: Inflation ; Imports ; Money supply ; ARDL model ; Toda-Yamamoto causality test.